Nanoelectronic primary thermometry below 4 mK - D. I. Bradley (Nature Portfolio, 2016)
When cooled to the millikelvin scale, nanoelectronic structures can become thermally detached from their environment, limiting nanoscale electronic thermometry. Here, the authors demonstrate the robust cooling of optimally-designed Coulomb blockade thermometer devices down to the millikelvin scale.